Exploring Dental Students’ Readiness for Inter-Professional Learning and Collaborative Practice: A Cross-Sectional Survey Study - Nasir, Saqif; Siddiqui, Saad Uddin; Qureshi, Sania; Saeed, Amber; Syed, Hamda; Wakar, Syeda Maliha; Abrar, Kashif (Journal of Liaquat University of Medical & Health Sciences, 2026)
Objective: To analyze the responses of participants to the readiness for inter-professional learning and collaborative practice questionnaire to determine their perceptions towards inter-professional learning. Methodology: A cross-sectional analytical study was conducted in a tertiary care hospital in Karachi to assess students’ attitudes and readiness for interprofessional learning using the Modified Readiness for Interprofessional Learning and Collaborative Practice questionnaire. Using PASS version 11, a minimum sample size of 42 per academic year was determined. The questionnaire consists of four subscales: teamwork and collaboration (items 1-9), negative professional identity (items 10-12), positive professional identity (items 13-16) and roles and responsibilities (items 17-19). Results: Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) Version 24. Means (M) and standard deviations (SD) were used to analyze and characterize the respondents’ demographic data. An independent sample t-test was used to evaluate gender differences, and a one-way ANOVA was used to assess differences across academic years. The P-value was set at 0.05. The overall response rate in our study was 95%. High mean scores for teamwork and collaboration were reported. No statistically significant differences were found across genders or academic years, except for negative professional identity. Conclusion: In our study, dental students showed a positive attitude toward inter-professional learning. Findings of the study suggest that embedding inter-professional education into the dental curriculum to enhance collaborative competencies and a culture of teamwork in the practice of future health care.